Bocor Alus Podcast: An Analysis of the Political Role of Media Tempo During the 2024 Presidential Election - W Suhaeb, Firdaus; Amsal, Bahrul; Wahda, Muhammad Aksha (Universitas Negeri Makassar, 2025)
This article aims to analyze how the media, particularly Tempo, plays a role in shaping the discourse of democracy during the 2024 Presidential Election in Indonesia. The main focus of this research is the analysis of the political role of the podcast program